2024
DOI: 10.1038/s41598-023-47933-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on determinants of carbon emissions from plaza ground paving during the construction stage based on life cycle assessment

Huayue Nie,
Lizhong Wang,
Meirong Tian

Abstract: The carbon emissions of paving projects are the focus of urban managers and researchers. By introducing the life cycle assessment (LCA) method and drawing up the study time and boundary, this study analyzed the carbon emissions activities of the plaza ground paving project and established a computational model of the cast-in-place architectural concrete (CAC) and natural stone pavement’s life cycle during the construction stage by comprehensively utilizing the carbon emission coefficient method and the direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…19 , can effectively reduce carbon emissions. This reduces energy consumption and minimizes the environmental impact of buildings, protecting the ecological environment 46 .
Figure 19 Carbon emission curves of concrete under different replacement rates.
…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…19 , can effectively reduce carbon emissions. This reduces energy consumption and minimizes the environmental impact of buildings, protecting the ecological environment 46 .
Figure 19 Carbon emission curves of concrete under different replacement rates.
…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…The outcomes revealed that the composite and concrete buildings produced more emissions than the steel structure. Nie et al 31 analyzed CO 2 emissions from plaza ground and found that the building main elements can contribute more than 70% of the total embodied emissions. Li et al 32 compared the carbon footprint in prefabricated buildings.…”
Section: Introductionmentioning
confidence: 99%